Unraveling the mechanistic links between blood pressure regulation and calcium-magnesium homeostasis: Insights into hypertension, hyperparathyroidism, and mineral disorders - Pritha Dutta; Anita T. Layton (PLoS ONE, 2026)
The systems regulating blood pressure and calcium-magnesium (Ca 2+ -Mg 2+ ) homeostasis are increasingly recognized to have clinically relevant interactions, where alterations in one can lead to significant changes in the other. In this study, we developed a computational model integrating blood pressure regulation and Ca 2+ -Mg 2+ homeostasis in a male rat. We simulated various conditions, including hypertension, Ca 2+ , Mg 2+ , and vitamin D 3 deficiencies, and primary hyperparathyroidism. Simulations of hypertension, induced by various stimuli like increased renin or aldosterone secretion, demonstrated significant effects on parathyroid hormone (PTH), calcitriol, renal Ca 2+ /Mg 2+ handling, and bone resorption. Dietary Ca 2+ , Mg 2+ , and vitamin D 3 deficiencies was predicted to elevate mean arterial pressure, with Mg 2+ deficiency having a stronger effect. Furthermore, the model predicted that primary hyperparathyroidism elevates PTH, Ca 2+ , and calcitriol, leading to increased mean arterial pressure and bone loss. Overall, this model provides valuable insights into the mechanistic links between blood pressure regulation and Ca 2+ -Mg 2+ homeostasis, offering insights into clinical conditions like hypertension and hyperparathyroidism.